The Effect of Nostalgia Marketing on Consumers' Purchase Intention - Adil Mahmood Alkhafagi, Yasir (Journal of Economics and Administrative Sciences, 2023)
The aim of this paper is to determine the effect of nostalgia marketing on consumers’ purchase intention and demographic factors. Nostalgia marketing is one of the marketing ideas that some organizations use it to attract customers by evoking memories or heritage in their minds. This method would affect the emotions and feelings of people, which may raise their desire to buy. The questionnaire was used as a tool for data collection, and it was distributed to a random sample of 512 individuals. A sample is a group of individuals who have seen small sculptures displayed in shops inside Babylon Mall in Baghdad. The small sculptures show the life of Baghdadis in the fifties and sixties of the last century. Statistical software was used for data analysis. The critical result of research indicates that there is a positive effect of nostalgia marketing on consumers’ purchase intention.